Pengaruh siklus hidup, profitabilitas, utang, dan ukuran perusahaan terhadap kebijakan dividen pada perusahaan indeks LQ45 di Indonesia - Giroth, Fiergil Kevin; Budiarso , Novi Swandari; Korompis , Claudia W. M. (Riset Akuntansi dan Manajemen Pragmatis, 2024)
This study aims to empirically examine the influence of life cycle, profitability, leverage, and firm size on dividend policy in LQ45 index companies for the 2021-2023 period. Life cycle is measured by RETE, profitability is measured by ROA, leverage is measured by DER, firm size is measured by total assets natural logarithms, and dividend policy is measured by DPR. This type of research is a quantitative research on influence using secondary data. The sampling technique used was probability sampling with the proportionate stratified random sampling method and produced 27 samples of companies from 45 companies. The data analysis technique used in this study is multiple linear regression. The results of the study partially show that the life cycle has an effect on dividend policy, and profitability, leverage and firm size have no effect on dividend policy. The results of the study simultaneously show that life cycle, profitability, leverage and firm size have an effect on dividend policy.